Complete mitochondrial genome of the endangered Prunus pedunculata (Prunoideae, Rosaceae) in China: characterization and phylogenetic analysis - Liu, Qian; Wu, Zinian; Tian, Chunyu; Yang, Yanting; Liu, Lemeng; Feng, Yumei; Li, Zhiyong (Frontiers in Plant Science, 2023)
Prunus pedunculata (Prunoideae: Rosaceae), a relic shrub with strong resistance and multiple application values, is endangered in China. Extensive research had been devoted to gene expression, molecular markers, plastid genome analysis, and genetic background investigations of P. pedunculata. However, the mitochondrial genome of this species has not been systematically described, owing to the complexity of the plant mitogenome. In the present research, the complete mitochondrial genome of P. pedunculata was assembled, annotated, and characterized. The P. pedunculata mitogenome is a circular molecule with a total length of 405,855 bp and a GC content of 45.63%, which are the smallest size and highest GC content among the known Prunus mitochondrial genomes. The mitogenome of P. pedunculata encodes 62 genes, including 34 unique protein-coding genes (PCGs, excluding three possible pseudogenes), three ribosomal RNA genes, and 19 transfer RNA genes. The mitogenome is rich in repetitive sequences, counting 112 simple sequence repeats, 15 tandem repeats, and 50 interspersed repetitive sequences, with a total repeat length of 11,793 bp, accounting for 2.91% of the complete genome. Leucine (Leu) was a predominant amino acid in PCGs, with a frequency of 10.67%, whereas cysteine (Cys) and tryptophan (Trp) were the least adopted. The most frequently used codon was UUU (Phe), with a relative synonymous codon usage (RSCU) value of 1.12. Selective pressure was calculated based on 20 shared PCGs in the mitogenomes of 32 species, most of which were subjected to purifying selection (Ka/Ks < 1), whereas ccmC and ccmFn underwent positive selection. A total of 262 potential RNA editing sites in 26 PCGs were identified. Furthermore, 56 chloroplast-derived fragments were ascertained in the mitogenome, ranging from 30 to 858 bp, and were mainly located across IGS regions or rRNA genes. These findings verify the occurrence of intracellular gene transfer events from the chloroplast to the mitochondria. Furthermore, the phylogenetic relationship of P. pedunculata was supported by the mitogenome data of 30 other taxa of the Rosaceae family. Understanding the mitochondrial genome characteristics of P. pedunculata is of great importance to promote comprehension of its genetic background and provides a basis for genetic breeding of Prunus.